Knowledge, attitude, and practice toward pediatric vitamin D deficiency among parents - Yu, Chunli; Cai, Jingjuan; Wang, Chunxiang; Luo, Yan; Fang, Jian (Frontiers in Pediatrics, 2024)
Objective: To investigate the knowledge, attitude, and practice (KAP) towards pediatric vitamin D deficiency (VitD) among parents and explore the risk factors of their knowledge, attitude, and practice. Methods: This cross-sectional study enrolled parents in our Hospital between November 2022 and January 2023. Results: A total of 621 valid questionnaires were collected in this study. The knowledge, attitude, and practice scores were 6.13 ± 3.07 (theoretical score range: 0-13), 31.13 ± 6.20 (theoretical score range: 9-45), and 27.47 ± 4.21 (theoretical score range: 9-45), respectively; the mean knowledge score was <60%, indicating poor knowledge. Commercial and service industry workers and a monthly income ≥ 5000 CNY were independently associated with sufficient knowledge (all P<0.05). The knowledge score, ethnic minorities, divorced/widows, and spouses with a master’s degree or above were independently associated with positive attitudes (all P<0.05). The attitude score, female, non-urban, undergraduate education, commercial and service industry worker, and office worker were independently associated with proactive practice (all P<0.05). Those characteristics could help design future KAP interventions on vitD deficiency. Conclusions: This study demonstrated poor knowledge, positive attitude, and proactive practice regarding pediatric VitD deficiency among parents. Targeted interventions and educational programs should be developed to improve parental knowledge.